Natural Diterpenoid Oridonin Ameliorates Experimental Autoimmune Neuritis by Promoting Anti-inflammatory Macrophages Through Blocking Notch Pathway - Xu, Lu; Li, Lei; Zhang, Chen-Yang; Schluesener, Hermann; Zhang, Zhi-Yuan (Frontiers in Neuroscience, 2019)
The diterpenoid compound, Oridonin, extracted from the Chinese herb, Rabdosia rubescens, possesses multiple biological activities and properties. Oridonin exhibited efficient anti-inflammatory activity by inducing a switch in macrophage polarization to the anti-inflammatory phenotype through inhibition of the Notch pathway in our in vitro study; therefore, its potential therapeutic effects were further investigated in the animal model of human Guillain-Barré syndrome (GBS) and other polyneuropathies - experimental autoimmune neuritis (EAN). Either preventive or therapeutic treatments with Oridonin greatly attenuated disease peak severity, suppressed paraparesis, shortened disease duration, and even delayed EAN onset. Progression of neuropathic pain, demyelination, inflammatory cellular accumulations, and inflammatory cytokines in peripheral nerves were significantly attenuated. Meanwhile, accumulation of immune cells in the spinal roots and microglial activation in the lumbar spinal cord were also reduced. Interestingly, Oridonin treatment significantly increased the proportion of anti-inflammatory macrophages and made them locally dominant among all infiltrated macrophages in the peripheral nerves. The down-regulation of local Notch pathway proteins, together with our in vitro results indicated their possible involvement. Taken together, our results demonstrated that Oridonin effectively suppressed EAN by attenuating local inflammatory reaction and increasing the proportion of immune regulating macrophages in the peripheral nerves, possibly through blockage of the Notch pathway, which suggests Oridonin as a potential therapeutic candidate for human GBS and neuropathies.